2019
DOI: 10.3390/cancers11071007
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Uveal Melanoma: Treatment Strategies and Survival—Results from the Dutch Melanoma Treatment Registry

Abstract: Uveal melanoma (UM) is the most common primary intraocular tumor in adults. Up to 50% of UM patients will develop metastases. We present data of 175 metastatic UM patients diagnosed in the Netherlands between July 2012 and March 2018. In our cohort, elevated lactate dehydrogenase level (LDH) is an important factor associated with poorer survival (Hazard Ratio (HR) 9.0, 95% Confidence Interval (CI) 5.63–14.35), and the presence of liver metastases is negatively associated with survival (HR 2.09, 95%CI 1.07–4.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Also, to the best of our knowledge, our cohort is the second largest one of patients receiving BSC for metastatic UM, and we are the first to stage them. We are aware of seven previous reports that included 11 to 191 patients with BSC [9,[20][21][22][23][24][25]. One of these studies also analysed prognostic factors and found, in line with us, that patients who received BSC had worse PS than actively treated [23].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Also, to the best of our knowledge, our cohort is the second largest one of patients receiving BSC for metastatic UM, and we are the first to stage them. We are aware of seven previous reports that included 11 to 191 patients with BSC [9,[20][21][22][23][24][25]. One of these studies also analysed prognostic factors and found, in line with us, that patients who received BSC had worse PS than actively treated [23].…”
Section: Discussionsupporting
confidence: 56%
“…There is no published survival data on consecutive patients managed with best supportive care (BSC) to allow historical comparison with those actively treated, although such data would be valuable for planning and analysing trials of metastatic UM, most of which continue to be non-randomised and non-comparative [8,9]. We report population-based OS according to previously validated prognostic stages [10] for patients with metastatic UM managed only with BSC.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands a registry has been set up that includes UM patients with metastases. Jochems et al [47] studied this cohort, consisting of 227 patients that were included between 2012 and 2018; 175 of these patients provided complete data. Cases that were eligible for local treatment of metastases (for example, surgical resection, isolated hepatic perfusion with melphalan, radiotherapy, radiofrequency ablation) showed the best survival, with a 1-year survival of 82%, versus 49% for systemic therapy and 28% for supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that especially young patients with a good WHO performance score and few metastatic sites are good candidates for local therapy. Although we do not know how many of the patients in their study [47] were included in our cohort, it is likely that there is overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Toutee et al analyze the survival benefit and the risk of visual loss associated with early proton beam radiotherapy [33]. Jochems and colleagues report on treatment strategies and survival of metastatic uveal melanoma patients based on the Dutch Melanoma Treatment Registry [35]. Tura et al provide data indicating that the therapeutic antibody ranibizumab, and not bevacizumab, suppresses metabolic activity, proliferation, and intracellular Vascular Endothelial Growth Factor A, VEGF-A, levels in uveal melanoma [38].…”
mentioning
confidence: 99%